Studies on the Nutritional Characteristics of some Commercial Wheat Varieties of Dry Land and Wet Land Grown in Sindh Province - Aasia Akbar Panhwar,; Saghir Ahmed Sheikh,; Benish Nawaz Mirani,; Mahvish Jabeen Channa ,; Samia Khanzada, (Journal of Pharmacy and Nutrition Sciences, 2014)
The present research was carried out to investigate the nutritional characteristics of some commercial wheat varieties of dry land and wet land grown in Sindh province during 2011-12 at Institute of Food Sciences and Technology, Faculty of Crop Production, Sindh Agriculture University Tandojam. Four irrigated land (Inqulab, TD-1, Sarsabz and kherman) wheat varieties and four dry land (TK-3, Marvi, PK-85, Sassi) wheat varieties were collected from their respective areas and subjected to chemical analysis. The bio-chemical characteristics of dry land and wet land wheat varieties differed significantly. Chemical analysis indicate that moisture (13.06%), protein (14.83%), dry gluten (9.03%), wet gluten (35.66%), gluten index (73.8%), starch (75.83%) and zeleny (68.66%) contents were recorded higher in wet land wheat varieties than those of dry land wheat varieties with moisture (12.66%), protein (11.9%), dry gluten (8.2%), wet gluten (32.93%), gluten index (64.53%), starch (68.66%) and zeleny (58.33%). This study reveals that availability of water and environmental factors are directly related with the nutritional characteristics of wheat varieties. This study clarify that wet land wheat varieties are better in the context of nutritional qualities.